Exploring Internal Character Traits as Predictors of Entrepreneurial Intentions among Economics Education Students - Fahreza W, Muhammad; Syarifuddin, Syarifuddin; Suarlin, Suarlin; Elpisah, Elpisah (Journal of Educational Science and Technology (EST), 2025)
Entrepreneurial interest plays a crucial role in shaping independent and innovative graduates, particularly in the field of economics education, where students are expected to lead entrepreneurial transformation. Recent evidence indicates a persistent gap between entrepreneurial awareness and actual entrepreneurial action among university graduates in Indonesia. This study aims to examine the predictive roles of internal religiosity, self-confidence, and sense of responsibility on students’ entrepreneurial interest. A quantitative approach with a correlational design was employed, involving 250 undergraduate students from Economics Education programs at two universities, selected using purposive probability sampling. Data were collected through a structured Likert-scale questionnaire and analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The findings reveal that all three independent variables internal religiosity, self-confidence, and sense of responsibility exert positive and significant effects on entrepreneurial interest, both individually and collectively. These results underscore the importance of integrating psychological and moral dimensions into efforts to enhance students’ readiness for entrepreneurial engagement. This study contributes to the enrichment of entrepreneurship education theory by incorporating a character-based psychological model and offers practical insights for curriculum developers to integrate value-based entrepreneurship training into higher education.